1993
DOI: 10.1016/0168-9274(93)90135-e
|View full text |Cite
|
Sign up to set email alerts
|

Parallel block predictor-corrector methods of Runge-Kutta type

Abstract: Van der Houwen, P.J. and Nguyen huu Cong, Parallel block predictor-corrector methods of Runge-Kutta type, Applied Numerical Mathematics 13 (1993) 109-123.In this paper, we construct block predictor-corrector methods using Runge-Kutta correctors. Our approach consists of applying the predictor-corrector method not only at step points, but also at off-step points (block points), so that, in each step, a whole block of approximations to the exact solution is computed. In the next step, these approximations are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In this way, r approximations are found in each step and this information is used to create a high-order prediction in the next step. Compared with the original PIRK method (i.e., with blocklength r = 1), a substantial increase in efficiency is reported in [17]. This idea is of course equally well applicable in the present context of second-order equations.…”
Section: The Order Of the Predictormentioning
confidence: 72%
See 1 more Smart Citation
“…In this way, r approximations are found in each step and this information is used to create a high-order prediction in the next step. Compared with the original PIRK method (i.e., with blocklength r = 1), a substantial increase in efficiency is reported in [17]. This idea is of course equally well applicable in the present context of second-order equations.…”
Section: The Order Of the Predictormentioning
confidence: 72%
“…The information needed to construct such a prediction could be obtained from approximations calculated in the preceding step. For example, in [17], van der Houwen and Nguyen huu Cong analyse (for first-order ODEs) a block version of the PIRK method [15] with the aim to construct a high-order prediction. The idea is to apply a PIRK method (which is very similar to a PIRKN method) not only with stepsize h, but, in addition (and simultaneously) with stepsizes h; = a;h, i = 1, ... , r -1.…”
Section: The Order Of the Predictormentioning
confidence: 99%
“…However, since the matrix Q is a Vandermonde one, the closeness of the abscissae will increase the magnitude of the entries of the matrix (Bs-k,8-k, B~-k,k, v), causing serious round-off errors in the approximated values. There are several ways to reduce this round-off effect (see Subsection 2.3 in [10]) but the most realistic option is to limit the minimal spacing of the abscissae of collocation vector c. It was found that on a Silicon Grafics Inc. Power Iris 4D/240S-64 machine with 15 digits precision, the abscissae should be separated by about 0.2 in order to suppress rotmding errors as muchas possible (cf. also [10]).…”
Section: The Choice Of the Methods Parametersmentioning
confidence: 98%
“…The rate of convergence of the IPIPTRK method (3.1) is defined by using the model test equation y (t) = λy(t), where λ runs through the eigenvalues of the Jacobian matrix ∂f/∂y (cf., e.g., [7,11,14,20]). Applying the IPIPTRK method (3.1) to this model test equation, we obtain the iteration error equation…”
Section: Rate Of Convergencementioning
confidence: 98%